Fingerprinting heterocellular β-adrenoceptor functional expression in the brain using agonist activity profiles - Matt, Rachel A.; Westhorpe, Frederick G.; Romuar, Rosemary F.; Rana, Payal; Gever, Joel R.; Ford, Anthony P. (Frontiers in Molecular Biosciences, 2023)
Noradrenergic projections from the brainstem locus coeruleus drive arousal, attentiveness, mood, and memory, but specific adrenoceptor (AR) function across the varied brain cell types has not been extensively characterized, especially with agonists. This study reports a pharmacological analysis of brain AR function, offering insights for innovative therapeutic interventions that might serve to compensate for locus coeruleus decline, known to develop in the earliest phases of neurodegenerative diseases. First, β-AR agonist activities were measured in recombinant cell systems and compared with those of isoprenaline to generate Δlog(Emax/EC50) values, system-independent metrics of agonist activity, that, in turn, provide receptor subtype fingerprints. These fingerprints were then used to assess receptor subtype expression across human brain cell systems and compared with Δlog(Emax/EC50) values arising from β-arrestin activation or measurements of cAMP response desensitization to assess the possibility of ligand bias among β-AR agonists. Agonist activity profiles were confirmed to be system-independent and, in particular, revealed β2-AR functional expression across several human brain cell types. Broad β2-AR function observed is consistent with noradrenergic tone arising from the locus coeruleus exerting heterocellular neuroexcitatory and homeostatic influence. Notably, Δlog(Emax/EC50) measurements suggest that tested β-AR agonists do not show ligand bias as it pertains to homologous receptor desensitization in the system examined. Δlog(Emax/EC50) agonist fingerprinting is a powerful means of assessing receptor subtype expression regardless of receptor expression levels or assay readout, and the method may be applicable to future use for novel ligands and tissues expressing any receptor with available reference agonists.